PATTERN OF DRUG UTILIZATION DURING PREGNANCY AT A TEACHING HOSPITAL – A PROSPECTIVE OBSERVATIONAL STUDY - MANASA MR,; SWETHA K, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study is (1) to assess the drug utilization pattern in pregnancy and (2) to assist in ensuring rational drug therapy. Methods: A prospective, cross-sectional observational study was conducted at the Obstetrics and Gynecology Outpatient Department of KRIMS, Karwar. 546 pregnant women aged 18–40 years were included. Data collected from prescriptions were analyzed for adherence to the World Health Organization core prescribing indicators and classified as per the US Food and Drug Administration (FDA) pregnancy categories. Results: The average age of study participants was 26.96 years with an urban preponderance (77.65%). Morning sickness (35.71%) and upper respiratory tract infections (20.7%) were the most frequent ailments encountered. 6383 drugs were prescribed in 2555 prescriptions with an average of 2.5 drugs per prescription. Iron and calcium supplements (28.75% each) were the most common drugs prescribed. 12.25% of prescriptions had fixed-dose combinations. 86.28% of drugs were from the National List of Essential Medicine (NLEM) and the majority of drugs belonged to FDA pregnancy category B (39.02%). Conclusion: Rational prescribing was demonstrated in our study by a fewer number of drugs per prescription and lesser utilization of antibiotics and injections. Generic names were commonly used and drugs were selected from NLEM. It is essential to prescribe medicines with established efficacy and safety to ensure maternal and fetal well-being.